2018
DOI: 10.1038/s41386-018-0032-x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired reward prediction error encoding and striatal-midbrain connectivity in depression

Abstract: Anhedonia (hyposensitivity to rewards) and negative bias (hypersensitivity to punishments) are core features of major depressive disorder (MDD), which could stem from abnormal reinforcement learning. Emerging evidence highlights blunted reward learning and reward prediction error (RPE) signaling in the striatum in MDD, although inconsistencies exist. Preclinical studies have clarified that ventral tegmental area (VTA) neurons encode RPE and habenular neurons encode punishment prediction error (PPE), which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
147
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(152 citation statements)
references
References 51 publications
(81 reference statements)
3
147
1
1
Order By: Relevance
“…Additionally, a range of studies have reported alterations in non-social learning in MDD. For instance, using decision-making tasks, it has been observed that depressed subjects display impaired reward learning (Blanco et al, 2013;Cooper et al, 2014;Herzallah et al, 2013;Kumar et al, 2018;Kunisato et al, 2012;Maddox et al, 2012;Pechtel et al, 2013;Robinson et al, 2012), while their punishment learning is either enhanced Maddox et al, 2012) or unchanged (Herzallah et al, 2013;Kumar et al, 2018;Kunisato et al, 2012;Robinson et al, 2012), when compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a range of studies have reported alterations in non-social learning in MDD. For instance, using decision-making tasks, it has been observed that depressed subjects display impaired reward learning (Blanco et al, 2013;Cooper et al, 2014;Herzallah et al, 2013;Kumar et al, 2018;Kunisato et al, 2012;Maddox et al, 2012;Pechtel et al, 2013;Robinson et al, 2012), while their punishment learning is either enhanced Maddox et al, 2012) or unchanged (Herzallah et al, 2013;Kumar et al, 2018;Kunisato et al, 2012;Robinson et al, 2012), when compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, it is possible that an enhanced ERN may protect early maturing anxious youth from developing depression. For instance, enhanced neural activity supporting the monitoring and salience of one’s performance could be an adaptive and compensatory response to the tendency of depressed individuals to exhibit reduced sensitivity to reward and reinforcement (Kumar et al, 2018). Future longitudinal designs would help to further unpack the emergence of internalizing symptom dimensions in relation to the neural changes occurring across the transition from pre- to post-pubertal status and in relation to the timing of when this transition occurs.…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with structural changes, MDD appears to produce functional aberrations in systems associated with reward processing. Evidence of differences in activation and connectivity in healthy individuals relative to those with MDD typically implicate the OFC (Cheng et al, 2018;Ng et al, 2019), the ventral striatum (VS; Furman et al, 2011;Kumar et al, 2018;Robinson et al, 2012), and the vmPFC (Koenigs et al, 2008;Myers-Schulz & Koenigs, 2012). Together, this work suggests that we may be able to understand some of the canonical symptoms seen in MDD symptomatology by taking a closer look at the neural correlates that underlie them.…”
Section: Introductionmentioning
confidence: 85%